Redefining Indonesia's MSMEs Landscape: Unleashing Digital Virality for Sustainable Growth - Dyatmika, Sutama Wisnu; Suyanto, Bagong; Setijaningrum, Erna; Setioningtyas, Widhayani Puri (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2023)
This study investigates the effectiveness of digital marketing strategies, particularly viral content, in enhancing the visibility and sustainability of micro, small, and medium enterprises (MSMEs) in Indonesia. By redefining the traditional MSME landscape, this research highlights the shift from conventional marketing approaches to digital virality strategies, reshaping how MSMEs engage with consumers and build sustainable brand identities. Adopting a descriptive qualitative approach, data was collected through a literature review and interviews with MSME stakeholders to analyze the digital marketing strategies used and their impacts. The findings reveal that viral content significantly boosts MSMEs' visibility by capturing consumer attention, fostering online engagement, and strengthening brand image. This study offers valuable insights for MSME owners and local governments and supports institutions in implementing effective digital strategies. Practical recommendations include developing skills in content creation, collaborating with local influencers, and utilizing social media platforms to maximize outreach. These findings underscore the potential of digital virality as a sustainable marketing tool while also recognizing limitations such as resource constraints. Future research may further explore adaptive strategies suited to different MSME sectors.